Case Report: Novel MFSD8 Variants in a Chinese Family With Neuronal Ceroid Lipofuscinoses 7 - Qiao, Yimeng; Gu, Yang; Cheng, Ye; Su, Yu; Lv, Nan; Shang, Qing; Xing, Qinghe (Frontiers in Genetics, 2022)
Neuronal ceroid lipofuscinoses (NCLs) are among the most common progressive encephalopathies of childhood. Neuronal ceroid lipofuscinosis 7 (CLN7), one of the late infantile-onset NCLs, is an autosomal recessive disorder caused by mutations in the MFSD8 gene on chromosome 4q28. Almost all reported mutations of MFSD8 in CLN7 patients were small mutations. However, we report a 4-year-old boy with CLN7 harboring compound heterozygous mutations in the MFSD8 gene, including one novel two-nucleotide deletion c.136_137delAT (p. M46Vfs*22) and one whole gene deletion of MFSD8 confirmed by Sanger sequencing, genomic quantitative PCR and CNV-seq. Therefore, for nonconsanguineous CLN7 patients with homozygous mutations in the MFSD8 gene, genetic counseling staff should focus on the possibility of whole gene deletion. This is one case report describing a whole gene deletion in a Chinese patient with CLN7, suggesting the diagnosis of CLN7 should be based on clinical suspicion and genetic testing.